Функціонування універбатів у мові інтернет-видання «Українська правда» на початку ХХІ ст. - Навальна, Марина Іванівна; Navalna, Marуna (Східноєвропейський національний університет, 2013)
У статті проаналізовано найуживаніші універбати, які функціонують у мові інтернет-видання «Українська правда», визначено їхні найпоширеніші тематичні групи, окреслено основні структурні особливості суфіксальних універбатів. The article analysed the most used univerbats, which function in language of Internet edition «Ukrainska pravda», defined their the most used thematic groups. Emphasized univerbats, which denote elected and public processes, objects of different newest technology, mechanisms, models of cars and so on. The article described the main structural features of suffixal univerbats, defined their stylistic role, concluded about language economy and diffusivity of lexical units in publicism, and also, univerbation as the way of derivation goes beyond only spoken language.
Functioning of Univerbats in Language of Internet Edition «Ukrainska Pravda» at the Beginning of XXI Century
Keywords: універбати; суфіксальні універбати; мова інтернет‑видання «Українська правда»; тематичні групи; univerbats; suffixal univerbats; мова інтернет‑видання «Українська правда»; language of Internet edition «Ukrainska pravda»; thematic groups; language economy